PERAN ORANG TUA DALAM PENGASUHAN ANAK - Ngewa, Herviana Muarifah (Institut Agama Islam Negeri Bone, 2019)
This article aims to describe the role of parents in childcare by preparing and planning an effective and high-quality parenting concepts for their children. Parents need to understand and pay attention to the importance of parenting patterns applied to their children such as authoritarian, permissive, democratic, and neglected parentings so that parents can know the impact of parenting patterns which were applied according to the needs of children. Â Keywords: The Role of Parents, Parenting